Detection of mecA Gene As a Marker for Staphylococcus aureus Types of Methicillin Resistant Staphylococcus aureus (MRSA) Using PCR Technique - Sari, Monica Ayu Retno; Qurrohman, Muhammad Taufiq; Dewangga, Vector Stephen (Jurnal Biologi Tropis, 2024)
Staphylococcus aureus is a Gram-positive bacterium responsible for various infections, showing strong resistance to β-lactam antibiotics due to the mecA gene, which encodes Penicillin-Binding Protein 2A (PBP2A). This resistance contributes to the emergence of Methicillin-Resistant Staphylococcus aureus (MRSA), posing significant challenges in clinical settings. Detecting the mecA gene is crucial for identifying MRSA and guiding appropriate treatments. This study aimed to detect the mecA gene in clinical pus samples from patients with MRSA infections in hospitals in Surakarta. A qualitative descriptive design was used. DNA was isolated from 12 clinical pus samples, and the mecA gene was detected using Polymerase Chain Reaction (PCR). Gel electrophoresis visualized the amplified DNA bands, and results were analyzed based on comparison with positive and negative controls and a DNA ladder. The results showed positive amplification of the mecA gene in all clinical samples, with clear DNA bands at 571 base pairs. One sample (SP1) and the positive control exhibited weaker bands, but the presence of the mecA gene was confirmed in all cases. The study concluded that all clinical samples were positive for the mecA gene, indicating the presence of MRSA. PCR proved to be an effective tool for detecting the mecA gene in clinical samples and is valuable for identifying MRSA in healthcare settings.